Penile involvement in Systemic Sclerosis: New Diagnostic and Therapeutic Aspects. (26th August 2010) - Aversa, Antonio; Bruzziches, Roberto; Francomano, Davide; Rosato, Edoardo; Salsano, Felice; Spera, Giovanni
Abstract : Systemic Sclerosis (SSc) is a connective tissue disorder featuring vascular alterations and an immunological activation leading to a progressive and widespread fibrosis of several organs such as the skin, lung, gastrointestinal tract, heart, and kidney. Men with SSc are at increased risk of developing erectile dysfunction (ED) because of the evolution of early microvascular tissutal damage into corporeal fibrosis. The entity of penile vascular damage in SSc patients has been demonstrated by using Duplex ultrasonography and functional infra-red imaging and it is now clear that this is a true clinical entity invariably occurring irrespective of age and disease duration and constituting the '' sclerodermic penis ''. Once-daily phosphodiesterase type-5 (PDE5) inhibitors improve both sexual function and vascular measures of cavernous arteries by improving surrogate markers of endothelial dysfunction, that is, plasma endothelin-1 and adrenomedullin levels, which may play a potential role in preventing progression of penile fibrosis and ED. Also, the beneficial effect of long-term PDE5i add-on therapy to SSc therapy in the treatment of Raynaud's phenomenon is described.